Effect of Gross Regional Domestic Product And Unemployment on Poverty Levels in Indonesia - Salfina, Lili; Sonia, Zakia; Murni, Yanti (Asean International Journal of Business, 2025)
This study aims to determine the Influence of Gross Regional Domestic Product (GRDP) and Unemployment on Poverty Levels in Indonesia. The type of research used in this study is quantitative data. The analysis technique used is panel data regression analysis. The estimation tool used in the study iseviews10 and the analysis selected for use in this study isFixed Effect Model(FEM). The results of the study show that the value of Y = 9.464451 + 0.144933X1 + 0.134832X2 and the partial results of the Gross Regional Domestic Product (GRDP) variable have a positive but insignificant effect on the Poverty Rate in Indonesia, meaning that an increase in GRDP is not necessarily able to directly reduce the poverty rate. Meanwhile, unemployment was found to have a positive and significant effect, meaning that the higher the unemployment rate, the higher the poverty rate. When both variables were analyzed together (simultaneously), both were shown to have a significant effect on poverty, indicating that this combination of macroeconomic factors is important to consider in poverty alleviation. The level of explanation of the model is also very high, with an Adjusted R Square of 99.3%, meaning that almost all variations in the poverty rate can be explained by changes in GRDP and unemployment, while only 0.7% is influenced by other factors not examined in this study.